Regroup and add. You got the 5n, so you should be able to get the other part!
n + n - 1 + n - 2 + n + 7 + n - 11 =
n + n + n + n + n - 1 - 2 + 7 - 11 =
5n - 7
Notice that -1 -2 - 11 = -14, add 7 to it and you get -7
NRT
2006-11-23 09:00:29
·
answer #1
·
answered by New Rule Tomorrow 2
·
1⤊
0⤋
n + n - 1 + n - 2 + n + 7 + n - 11=5n-7
2006-11-23 18:26:32
·
answer #2
·
answered by yupchagee 7
·
0⤊
0⤋
The something is -1 - 2 + 7 -11. So the answer is 5n - 7.
2006-11-23 18:09:56
·
answer #3
·
answered by steiner1745 7
·
0⤊
0⤋
Addition of scalars is commutative. So it's 5n - 1 - 2 + 7 - 11 = 5n -14 +7 = 5n -7
2006-11-23 17:01:40
·
answer #4
·
answered by Edgar Greenberg 5
·
0⤊
0⤋
n + n - 1 + n - 2 + n + 7 + n - 11
= n + n + n + n + n + 7 - 1 - 2 - 11
= 5n + 7 - 14 (+7 - 14 = opposite of + 14 - 7 = opposite of + 7 = - 7)
= 5n - 7
2006-11-23 17:00:31
·
answer #5
·
answered by Wal C 6
·
0⤊
0⤋
And the something is -1-2+7-11 = -7. So 5n-7.
2006-11-23 17:00:16
·
answer #6
·
answered by stephen m 4
·
0⤊
0⤋
Add like terms
(n+n+n+n+n) + (-1+-2++7+-11)=
5n-7
2006-11-23 21:45:37
·
answer #7
·
answered by lulu 3
·
0⤊
0⤋
Well, inorder to solve this problem you have to combine like terms. so you'll take n+n-1+n-2+n+7+n-11and combine the variables and the whole numbers.
n+n-1+n-2+n+7+n-11=(n+n+n+n+n)+(-1+-2+7+-11)
n+n-1+n-2+n+7+n-11=(5n)+(-7)
n+n-1+n-2+n+7+n-11= (5n-7)
2006-11-23 17:17:48
·
answer #8
·
answered by Carpe Diem (Seize The Day) 6
·
0⤊
0⤋
n+n+n+n+n =5n
-1-2+7-11 = -7
answer: 5n-7
2006-11-23 17:17:45
·
answer #9
·
answered by dragon888c 2
·
0⤊
0⤋
let's simplify this down.
(n+n+n+n+n)+(-1-2+7-11)
(5n)+(-3+7-11)
(5n)+(4-11)
5n-7
2006-11-23 17:03:36
·
answer #10
·
answered by Hawk 2
·
0⤊
0⤋